Factors associated with risk of COVID-19 contagion for endoscopy healthcare workers: A survey from the Italian society of digestive endoscopy. Issue 5 (May 2021) - Mariani, Alberto; Capurso, Gabriele; Marasco, Giovanni; Bertani, Helga; Crinò, Stefano Francesco; Magarotto, Andrea; Tringali, Andrea; Pasquale, Luigi; Arcidiacono, Paolo Giorgio; Zagari, Rocco Maurizio
Abstract: Background and aims: The present study was aimed to assess the risk of SARS-CoV-2 infection and associated factors among HCWs in endoscopy centers in Italy. Methods: All members of the Italian Society of Digestive Endoscopy (SIED) were invited to participate to a questionnaire-based survey during the first months of the COVID-19 outbreak in Italy. Results: 314/1306 (24%) SIED members accounting for 201/502 (40%) endoscopic centers completed the survey. Personal Protection Equipment (PPE) were available in most centers, but filtering face-piece masks (FFP2 or FFP3) and negative pressure room were not in 10.9 and 75.1%. Training courses on PPE use were provided in 57.2% of centers only; there was at least one positive HCW in 17.4% of centers globally, 107/3308 (3.2%) HCWs were diagnosed with COVID-19 with similar rates of physicians (2.9%), nurses (3.5%) and other health operators (3.5%). Involvement in a COVID-19 care team (OR: 4.96) and the lack of training courses for PPE, (OR: 2.65) were associated with increased risk. Conclusions: The risk of COVID-19 among endoscopy HCWs was not negligible and was associated with work in a COVID-19 care team and lack of education on proper PPE use. These data deserve attention during the subsequent waves.